Telomere - A Complex End of a Chromosome 2016
DOI: 10.5772/64713
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Its Relation to Human Health

Abstract: Telomeres are complex nucleotide sequences that cap the end of chromosomes from degradation, unwanted recombination-fusion, inappropriate activation of DNA damage response and play a critical role in cell division and chromosome stability. There is growing evidence that telomere stability can be affected by occupational and environmental exposure, as some of these factors have been correlated with increase in inflammation, oxidative stress, DNA damage, chromosome aberration, and epigenetic alterations. Both ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 121 publications
(188 reference statements)
0
11
0
Order By: Relevance
“…Our study differs from this one because participants from the current work, whether exposed or not, had appropriate intake of folate and B 12 . This adds to growing evidence that, actually, there is a complex relationship of telomere length with B vitamins (reviewed by [ 24 ]). In the general US population exposed to cadmium, leukocyte telomere length was found to be decreased and a diet pattern was also evaluated.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Our study differs from this one because participants from the current work, whether exposed or not, had appropriate intake of folate and B 12 . This adds to growing evidence that, actually, there is a complex relationship of telomere length with B vitamins (reviewed by [ 24 ]). In the general US population exposed to cadmium, leukocyte telomere length was found to be decreased and a diet pattern was also evaluated.…”
Section: Discussionmentioning
confidence: 83%
“…In our study, there was no significant difference in folate between nonexposed and exposed groups; still, vitamin B 12 , measured in serum, was significantly elevated for farmers, and yet, a decrease in telomere length was found for the same group. In other study, folate deficiency leads to long but dysfunctional telomeres, associated with higher chromosome instability, probably due to DNA hypomethylation (reviewed by [ 24 ]). Paul et al [ 59 ] observed that levels of folate above the median have a positive correlation with telomere length.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations